2021
DOI: 10.3390/v13010090
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acid Lipid Metabolism Nexus in COVID-19

Abstract: Enteric symptomology seen in early-stage severe acute respiratory syndrome (SARS)-2003 and COVID-19 is evidence of virus replication occurring in the intestine, liver and pancreas. Aberrant lipid metabolism in morbidly obese individuals adversely affects the COVID-19 immune response and increases disease severity. Such observations are in line with the importance of lipid metabolism in COVID-19, and point to the gut as a site for intervention as well as a therapeutic target in treating the disease. Formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 147 publications
(180 reference statements)
1
80
0
Order By: Relevance
“…It is very well known that virus ramps up the fatty acid synthesis to support its growth i.e. synthesis of viral membranes [43]. For all the reactions in the fatty acid biosynthesis pathways, we see a high flux through them.…”
Section: Plos Computational Biologymentioning
confidence: 91%
“…It is very well known that virus ramps up the fatty acid synthesis to support its growth i.e. synthesis of viral membranes [43]. For all the reactions in the fatty acid biosynthesis pathways, we see a high flux through them.…”
Section: Plos Computational Biologymentioning
confidence: 91%
“…Researchers have investigated the beneficial use of treating COVID-19 using metformin, a biguanide derivative used to treat type 2 diabetes mellitus (T2DM), due to its antiviral and anti-inflammatory properties [ 171 ]. Studies have suggested that metformin activates the AMPK cascade by forming v-ATPase/Ragulator complex, which is associated with LKB1 and axis inhibition protein 1 (AXIN1), thus leading to AMPK activation and inhibition of mTORC1 [ 172 , 173 ]. Other suggested mechanisms of metformin inhibition of SARS-CoV-2 may occur with respect to its interaction with angiotensin converting enzyme 2 receptor (ACE2) following the activation of AMPK.…”
Section: Ampk and Covid-19mentioning
confidence: 99%
“…Metformin may enhance the phosphorylation of ACE2, leading to a conformational change and decrease binding and entry of SARS-CoV-2 [ 174 , 175 ]. Other mechanisms of metformin action are through AMPK-dependent reduction in lipid storage, increased fatty acid oxidation, and inhibition of glycolysis and lipogenesis [ 172 ]. SARS-CoV-2 was reported to increase the production of lipid anabolic enzymes including fatty acid synthase (FASN), a key regulator in palmitate synthesis and acetyl-CoA carboxylase (ACC1), which plays a key role in palmitoylation of proteins by increasing the activity of the PI3K/AKT/mTOR/S6K signaling pathway [ 172 , 176 ].…”
Section: Ampk and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations